Cerne e alburno em eucaliptos: influência da espécie e da idade nas propriedades tecnológicas - Cherelli, Sabrina Galetti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
One characteristic that mostly differentiates wood regions of a tree is the formation of heartwood and sapwood. The conceptual bases that established the precise definition and general physiological aspects involved in the formation of sapwood and heartwood were consolidated in the 60s, 70s and 80s of the last century. More recently, the studies have mainly focused the heartwood volume determination related to position along the stem and age of trees. This study aims to deeply knowledge about heartwood and sapwood from young (ages 2-6 years) and old trees (older than 18 years) of Eucalyptus sp., trying to determine, for young trees, the initial age of heartwood characterization, characteristics that are mostly affected in heartwood by aging and tree development site and, for old trees, the properties that are mostly affected in heartwood depending the species. Were evaluated young trees of two clones of different productivity in two sites of different performances and adult trees of E. grandis Hill ex. Maiden, E. saligna, E. tereticornis and C. citriodora. In young and adult trees were performed anatomical analyzes (macroscopic) for distinction between heartwood and sapwood, physical analysis (basic density, apparent density and densitometric radial profiles) and chemical analysis in each of the portions of the wood. In adult trees were also performed shrinkage tests, Janka hardness and compression parallel to grain in each portion of the wood studied. This study has some particular characteristics discerning from previous studies, highlighting the possibility of studying samples of clonal plantations (characterizing environmental effect, therefore) and contemporary analytical techniques, which are more potent and effectiveness, whereby the GC-MS – gas chromatography – mass spectrometry. The results for young Eucalyptus trees show that at two years of age they already had heartwood capable ...

Uma das características que mais diferencia as porções de lenho de uma árvore é a formação de cerne e alburno. As bases conceituais que permitiram a definição precisa e os aspectos fisiológicos gerais envolvidos na formação de alburno e cerne foram consolidadas nas décadas de 60, 70 e 80 do século passado. Em tempos mais recentes os estudos focaram, sobretudo, a determinação do volume de cerne relacionado à posição ao longo do fuste e à idade das árvores. Este estudo teve como objetivo aprofundar o conhecimento sobre o cerne e alburno de árvores jovens (idades de 2 a 6 anos) e adultas (idades superiores a 18 anos) de Eucalyptus sp., buscando determinar, para as árvores jovens, a idade inicial de caracterização do cerne, as características que mais se alteram no cerne com a idade e sítio de desenvolvimento da árvore e, para as árvores adultas, as propriedades que mais se alteram no cerne em função da espécie. Foram avaliadas árvores jovens de dois clones de diferentes produtividades em dois sítios de diferentes desempenhos e árvores adultas das espécies E. grandis Hill ex. Maiden, E. saligna, E. tereticornis e C. citriodora. Nas árvores jovens e adultas foram realizadas análises anatômicas (macroscópicas) para distinção entre cerne e alburno, análise física (densidade básica, densidade aparente e perfil densitométrico radial) e análise química em cada uma das porções do lenho. Nas árvores adultas foram ainda realizados ensaios de retratibilidade, dureza Janka e compressão paralela às fibras em cada uma das porções do lenho estudadas. Pela sua oportunidade o estudo apresentou algumas características particulares que o diferenciou dos estudos já realizados, destacando-se a possibilidade de estudar amostras de plantios clonais (e, com isso, melhor caracterizar o efeito do ambiente) e o uso de técnicas analíticas contemporâneas, de maior potencial ...
Heartwood and sapwood in eucalyptus: species and age influence on the technological properties
Keywords: Eucalipto - Fisiologia; Troncos (Botanica); Arvores - Crescimento; Plantas lenhosas; Woody plants Anatomy